Phenology of Douglas-Fir Beetle (Coleoptera: Curculionidae) and Its Role in Douglas-Fir Mortality in Western Washington. Issue 1 (10th December 2019) - Freeman, Michael B; Labarge, Amy; Tobin, Patrick C
Abstract: Douglas-fir dominated forests are an integral part of the Pacific Northwest. In the Cedar River Municipal Watershed, Washington, these forests provide erosion control and ecosystem buffering for the Cedar River system that supplies high-quality drinking water to the Seattle area. Mortality of Douglas-fir in the watershed has been increasing in recent years. The Douglas-fir beetle, Dendroctonus pseudotsugae Hopkins, as well as fungal pathogens, are key agents of mortality in Douglas-fir dominated forests, but their contributions to the current rates of mortality are unknown. We modeled D. pseudotsugae phenology in western Washington and estimated peak flight of overwintering adults at 344.5 cumulative degree-days (base temperature threshold = 4.3°C). We extended the results from the phenology model when assuming a 1.7°C increase in temperature and estimated that D. pseudotsugae adult flight could be advanced by 21–27 d. We also conducted a field study over 2 yr to quantify the individual and interacting roles of D. pseudotsugae, root rot pathogens, and other abiotic and biotic variables as drivers of Douglas-fir mortality. Study sites with recent high rates of mortality of Douglas-fir (>30%) were generally in lower elevation stands and affected by both D. pseudotsugae and root rot pathogens. Attacks by D. pseudotsugae in 1 yr were significantly associated with the presence of root rot mycelia in the following year, but not vice versa. The development of a D. pseudotsugae phenology model for the region and the identification of variables associated with Douglas-fir mortality facilitates the development of management strategies.